Digitalization Of Name Plate Equipment PLTU Pangkalan Susu Using Qr Code - Zulfahmi Syahputra; Wirda Fitriani; Ajie Maulizar (Sean Institute, 2021)
The primary purpose of this innovation is to prevent equipment specification errors. This innovation is conducted by pouring the contents of the specification into a QR code, where the data will be stored in the database. The database for this research uses google drive media. We carried it out using a direct field survey method. The results showed that the specifications of equipment are easily damaged, if it is poured into written form on a nameplate that uses iron material. Further, it is easy to cause corrosion which will cause data errors when an audit will be carried out or when replacing the equipment. This innovation utilizing QR codes provides a breakthrough to validate equipment specifications.